Associations between serum mineral metabolism parameters and mortality in patients on peritoneal dialysis. Issue 11 (29th April 2019) - Wu, Meiju; Wu, Haishan; Huang, Xuan; Ye, Hongjian; Huang, Fengxian; Yu, Xueqing; Yang, Xiao
ABSTRACT: Aim: Disturbances in mineral metabolism markers are common in patients with chronic kidney disease but there is no consensus on the association between these markers and clinical outcomes. This study investigated associations between mineral metabolism parameters and mortality in Chinese peritoneal dialysis (PD) patients. Methods: This was a single‐centre retrospective cohort study. Incident PD patients between 1 January 2006 and 31 December 2013 with baseline phosphate, albumin‐corrected calcium, and calcium‐phosphate product data were enrolled. Associations between these parameters and all‐cause and cardiovascular mortality were assessed using multivariable‐adjusted Cox models. Results: Of 1662 patients (mean age: 47.4 ± 15.3 years), 59.3% were male and 23.8% had diabetes. Over a median 38.1 month (interquartile range: 21.3–59.7 months) follow‐up period, 382 (23.0%) patients died. After adjusting for confounders, the higher serum phosphate level (>1.78 mmol/L) and calcium‐phosphate product level (≥4.4 mmol 2 /L 2 ) were significantly associated with an increased risk for all‐cause mortality (hazards ratio (HR) = 1.818, 95% CI = 1.379–2.396 and HR = 1.735, 95% CI = 1.261–2.386) and cardiovascular mortality (HR = 2.069, 95% CI = 1.428–2.998 and HR = 2.175, 95% CI = 1.450–3.262), respectively. While each 1 mmol/L higher baseline albumin‐corrected calcium level was associated with an 14.3% (95% CI = 0.749–0.981) lower risk for all‐cause mortality after adjusting for potential confounders. Conclusion: Abnormalities in mineral metabolism markers, particularly higher serum phosphate and calcium‐phosphate product levels, at the commencement of PD were independently associated with increased all‐cause and cardiovascular mortality in this cohort of PD patients. SUMMARY AT A GLANCE: The authors showed that high serum phosphate at the commencement of peritoneal dialysis was independently associated with increased all‐cause and cardiovascular mortality in a sizeable cohort of over 1, 600 patients.